2010
DOI: 10.1371/journal.pone.0009552
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Analysis of Ehrlichia chaffeensis Tandem Repeat Proteins Reveals Evidence of Phosphorylation and Absence of Glycosylation

Abstract: Background Ehrlichia chaffeensis has a small subset of immunoreactive secreted, acidic (pI ∼4), tandem repeat (TR)-containing proteins (TRPs), which exhibit abnormally large electrophoretic masses that have been associated with glycosylation of the TR domain.Methodology/Principal FindingsIn this study, we examined the extent and nature of posttranslational modifications on the native TRP47 and TRP32 using mass spectrometry. Matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 57 publications
(72 reference statements)
3
39
0
Order By: Relevance
“…A tyrosine-rich C-terminal domain conserved between TRP75 and TRP95 had three predicted tyrosine phosphorylation sites, suggesting that this region is modified by phosphate. This finding is consistent with our previous reports demonstrating that TRP47 is also tyrosine phosphorylated (28). The TRP47 interacts with the host cell tyrosine kinase Fyn, and it appears that TRP75 may also be secreted to a location where it interacts with host cell tyrosine kinase(s).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A tyrosine-rich C-terminal domain conserved between TRP75 and TRP95 had three predicted tyrosine phosphorylation sites, suggesting that this region is modified by phosphate. This finding is consistent with our previous reports demonstrating that TRP47 is also tyrosine phosphorylated (28). The TRP47 interacts with the host cell tyrosine kinase Fyn, and it appears that TRP75 may also be secreted to a location where it interacts with host cell tyrosine kinase(s).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with other TRPs, the native TRP orthologs in this report migrated electrophoretically with larger than the predicted masses. Furthermore, the recombinant TR and C-terminal regions also migrated electrophoretically with larger than predicted masses, We have previously reported the relationship between acidic TRPs and abnormal migration (28) and demonstrated that these charged regions are associated with larger electrophoretic masses, a characteristic associated with incomplete SDS binding (6,28). We observed abnormal migration of recombinant protein fragments representing the TR region (pI 10) and the acidic (pI 4) C-terminal region, indicating that each of these regions contributes to the abnormal electrophoretic mobility.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations